Innovative application of ICT tools for paperless data capture and feedback in smallholder dairy production systems: The platform for Africa Dairy Genetic Gains (ADGG) - Okeyo Mwai, Ally; Ojango, Julie M.K.; Mrode, Raphael A.; Quirós, C.; Gibson, John P.; Efa, Kefena; Besufekad, J.; Lyatuu, Eliamoni T.R.; Msuta, G.; Kahumbu Stephanou, Su; Nyakundi, H.N.; Mogaka, D.; et al. (International Livestock Research Institute, 2019)
Functioning national livestock performance recording and monitoring systems are scarce in Sub-Saharan Africa, yet improvements and changes in any livestock sector heavily depend on the availability of information and accurate data on animal characteristics and their performance within different production environments. Constraints to the adoption of livestock recording in Africa include inadequate policies and poor infrastructure; weak organizations and institutions; small and dispersed herds; limited capacity and understanding of livestock recording processes; and lack of appropriate incentives for farmers to share records. In recent times, ICT tools, notably mobile telephony systems have greatly advanced, and if adequately utilized can transform data capture, sharing and use for small- holder livestock keepers. This paper presents the development and piloting of a livestock recording, monitoring and feedback system in Tanzania and Ethiopia as part of the platform for Africa Dairy Genetic Gains (ADGG), which is supported by the Bill and Melinda Gates foundation. It specifically focuses on the tools and the data collation platform, and on the results to date. Within the first two years of the project, more than 70,161 animals, from 45,000 small holder farmers in Tanzania and Ethiopia have been registered and are being monitored on the ADGG platform. In a unique public-private partnership with the Green-Dreams Tech, the ADGG platform has integrated an SMS system that is providing feedback information to the farmers from the data in the two countries. The ADGG platform is envisioned to be adopted by other countries in Africa.